Chemical Composition, Antioxidant Potential, and Blood Glucose Lowering Effect of Aqueous Extract and Essential Oil of Thymus Serrulatus Hochst. Ex Benth - Haile, Tesfay; Cardoso, Susana M.; de Oliveira Raphaelli, Chirle; Pereira, Olívia R.; Pereira, Elisa dos Santos; Vizzotto, Márcia; Nora, Leonardo; Asfaw, Adissu Alemayehu; Periasamy, Gomathi; Karim, Aman (Frontiers in Pharmacology, 2021)
Thymus serrulatus, an endemic plant of Ethiopia, is traditionally used to cure various diseases and as a food ingredient. In the Ethiopian folk medicine, the decoction is orally taken as a remedy to treat diabetes and blood pressure. The purpose of the present study was to evaluate the antioxidant and antihyperglycemic effect of the aqueous extract and the essential oil of Thymus serrulatus. The chemical composition of the aqueous extract was determined by LC-MS and the essential oil were characterized by GC-MS analysis. Radical scavenging assays, namely scavenging of 2,2-diphenyl-1-picrylhydrazyl (DPPH•), hydroxyl (•OH) and nitric oxide (•NO), were used as a first approach to screen the potential antioxidant abilities of the samples. Alpha-amylase and α-glucosidase inhibitory studies were also employed to evaluate the in vitro antihyperglycemic potential of the plant. In vivo blood glucose lowering effect of the extracts was assessed using hypoglycemic activity and the oral glucose tolerance test in normal and in streptozotocin (STZ)-induced diabetic mice. When compared to the aqueous extract, the essential oil showed superior radical scavenging activity, particularly for •NO, as well as greater inhibitory potency against α-amylase (IC50 = 0.01 mg/mL) and α-glucosidase (IC50 = 0.11 mg/mL). Both tested samples showed a statistically significant antihyperglycemic effect. The aqueous extract at 600 mg/kg exerted maximum antihyperglycemic activity (44.14%), followed by the essential oil (30.82%). Body weight and glucose tolerance parameters were also improved by the samples both in normal and diabetic mice. The findings of this study support the hypothesis that aqueous extract and essential oil of T. serrulatus are promising therapeutic agents.